(Training to Prevent Sports Injuries to Ankles for Football Athletes) - Soemardiawan, Soemardiawan; Yundarwati, Susi (Abdi Masyarakat, 2024)
The problem is that the incidence of ankle injuries in soccer athletes at soccer clubs in West Nusa Tenggara dominates every year, and experiences a decline in performance due to ankle injuries. The aim of this service is to analyze ankle injuries in NTB football players by identifying injuries through the coaches, medical team who provide information to the physiotherapy team. The method used in this research design is observational with a case control design with a retrospective study with the aim of finding out training to prevent sports injuries to the ankle for football athletes. Research stages: Screening Questionnaire and Ankle examination form, Initial examination 1, Examination management 1 and Seminar workshop. Research Results Based on the results and discussion in this research, it can be concluded that: there is a very significant effect of sports injury prevention training on the ankle for football athletes after chronic ankle injury.